5ц 4/13 — х = 4ц 5/13

5ц 4/13 - х = 4ц 5/13

  • 5ц4 / 13-х = 4ц5 / 13
    х = 5ц4 / 13-4ц5 / 13
    х = 12 / 13ц
  • 5 4/13 - x = 4 5/13
    x = 5 4/13 - 4 5/13
    x = 4 17/13 - 4 5/13
    x = 12/13
    Відповідь: х = 12/13
    Перевірка:
    5 4/13 - 12/13 = 4 17/13 - 12/13 = 4 5/13

Понравилась статья? Поделись с друзьями:
Добавить комментарий

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

30 − 21 =